Evaluation of Some Plant Fruit Extracts for the Control of West Nile Virus Vector Culex pipiens (Diptera: Culicidae) - Samed Koc; Ozay Hasan Evren; Huseyin Cetin (Tehran University of Medical Sciences, 2016)
Background:  The extracts of different parts of plants were found very effective against various pests. The aim of this research was to determine the insecticidal activity of fruit methanol extracts obtained from Melia azedarach (Meliaceae), Phoenix theophrasti (Arecaceae), Styphnolobium japonicum (Fabaceae) and Pyracantha coccinea (Rosaceae) against the larvae of Culex pipiens (Diptera: Culicidae). Methods: The fruits of test plants were collected from the Campus of Akdeniz University, Antalya, Turkey in 2013. A series of concentrations of the extracts ranging from 62.5-1000 ppm were tested against second instar larvae. Results: Only the extracts of Me. azedarach and Ph. theoprasti showed significant larvicidal activity against Cx. pipiens and the LC50 values of these extracts were found to be 169.48 and 220.60 ppm, respectively. This is the first research investigating the insecticidal or larvicidal activity of Ph. theophrasti, St. japonicum and Py. coccinea extracts on mosquitoes. Conclusion: The methanol extract of fruits of Me. azedarach and Ph. theophrasti showed significantly higher larvicidal activity against Cx. pipiens.